The Influence of Emotional Intelligence in promoting the Empowerment of Employees - محمد, سناء عريبي (Journal of Economics and Administrative Sciences, 2020)
The subject of the research seeks to indicate the level of influence of emotional intelligence in the empowerment of workers in the Ministry of Industry and Minerals General Company for Food Products. The research problem is illustrated by knowing all of the following:The level of the relationship between emotional intelligence in promoting the empowerment of employees of the Ministry of Industry and Minerals.The impact of emotional intelligence on the empowerment of workers in the ministry.Recognize the interest of the management of the Ministry of Industry and Minerals in emotional intelligence and the empowerment of workers and its variables? To achieve the goal of the research, a sample of individuals working in the administrative levels was surveyed from the directors and officials of the people in the ministry. The number of respondents was (57) employees. The research adopted the descriptive-analytical method and the questionnaire was used as a data collection tool based on the statistical analysis program. The research reached a number of conclusions, the nature of the relationship and influence between the variables of the research was the most important and the existence of a direct correlation between the emotional intelligence and the empowerment of workers as well as the existence of the relationship of moral influence between the variables. The research concluded a set of recommendations to the relevant authorities, including the possession of administrative leaders in the Ministry of the researched skills of emotional intelligence and use inappropriate situations and this enhances the requirements for the empowerment of employees and their use of those skills in a timely manner.